Humanismo romanista y paralelismo intercultural entre los anticuarios andaluces y el Inca Garcilaso - Pino-Díaz, Fermín Del (2014)
This article examines the Andalusian stage in the life of the author of the Comentarios Reales, as the original context of its creation. This literary context involves both its discursive nature (description of a culturally sufficient scenario, in dialogue with the reader) and its nationalist legitimation (the claim of an identity within the Christian Commonwealth). Such legitimation receives its characteristic mark of Renaissance logic (so common to the European nationalist process, from the fourteenth to the nineteenth century), but, more specifically, as a particular process of legitimizing stigmatized societies. In that sense, Andalucía, full of conversos incorporated into the Christian world (in Jewish and morisco minorities who claimed the right of Christian affiliation, recognized above all in the Society of Jesus until 1593) offered an ideal model for revindicating the despised, pre-Christian America (the Incas).